2001
DOI: 10.1002/jae.611
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linear error correction and the UK demand for broad money, 1878–1993

Abstract: SUMMARYIn this paper we reconsider an error-correction model of UK broad money demand by Ericsson, Hendry and Prestwich. Their model is non-linear in both variables and parameters, and it can be viewed as an approximation to a smooth transition regression (STR) type specification. The corresponding STR model, when specified and estimated, fits the data better than the original model. Adopting a somewhat more general modelling approach leads to another STR model. This model variance dominates the other two, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 11 publications
5
35
0
Order By: Relevance
“…The model proposed is shown to be stable over the full sample period examined and the finding of significant nonlinearity in the empirical money demand equation is consistent with several related empirical studies (e.g., inter alia, Hendry and Ericsson, 1991a;Lütkepohl, Teräsvirta and Wolters, 1999;Sarno, 1999;Teräsvirta and Eliasson, 2001).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The model proposed is shown to be stable over the full sample period examined and the finding of significant nonlinearity in the empirical money demand equation is consistent with several related empirical studies (e.g., inter alia, Hendry and Ericsson, 1991a;Lütkepohl, Teräsvirta and Wolters, 1999;Sarno, 1999;Teräsvirta and Eliasson, 2001).…”
Section: Introductionsupporting
confidence: 86%
“…The resulting model displays insignificant diagnostics (including the appropriate parameter constancy test), yielding a sizable reduction in the residual variance relative to the best fitting linear ECM (about 15 percent). Nevertheless, using the minimal nesting strategy of Mizon and Richard (1986) and applying a simplification encompassing test between the STR model given in Table 3 and the best fitting linear ECM in Table 1 as done, for example, in Sarno (1999) and Teräsvirta and Eliasson (2001), indicated that the nonlinear ECM does not encompass the linear ECM at the five percent significance level (although it does at the one percent level) without being encompassed.…”
Section: Panel B Ofmentioning
confidence: 99%
“…Both studies have found a clear structural instability that occurred in 1990, the year of German uni-® cation, and a signi® cant asymmetric eOE ect of the in¯ation rate on the demand for money. Other STECM studies by Tera È svirta and Eliasson (1998), and by Sarno (1999) also ® nd similar nonlinear dynamics in the demand for money in UK and Italy.…”
Section: Introductionsupporting
confidence: 54%
“…Similar models to equation (10) but with the possibility of affecting all the dynamic parameters are for example discussed in Teräsvirta and Eliasson (2001).…”
Section: Model 8: Double Threshold Logistic Error Correction Models (mentioning
confidence: 99%